Introduction to probability and statistics for engineers and scientists - Ross, Sheldon M. (Academic Press, 2000)
Suited for a first course in applied probability and statistics for engineering or science majors, this is a superior textbook. Introduction to Probability and Statistics for Engineers and Scientists, Second Edition, includes expanded coverage of quality control, and offers unique software that automates the computations required for exercises, as well as illustrating the main concepts of probability. The author emphasizes the manner in which probability yields insight into statistical problems; ultimately resulting in an intuitive understanding of the statistical procedures most often used by practicing engineers and scientists. Real data sets are incorporated in a wide variety of exercises and examples throughout the book, and this emphasis on data motivates the probability coverage.